Variation of extractable compounds and lignin contents in wood fragments used in the aging of wine brandies - Anjos, O. (2013)
Aging systems of wine brandies have been a target of investigation to reduce the costs and aging time. In this study, the extractives and Klason lignin contents of wood fragments used in the aging of wine brandies in stainless steel tanks were evaluated. Two types of wood fragments, known as staves and tablets, and two wood botanical species, Limousin oak (Quercus robur L. from the Limousin region of France) and Portuguese chestnut (Castanea sativa Mill.), with heavy toasting levels were used. The wood extractive and Klason lignin contents were analyzed before and 30 months after the aging of wine brandy. The results showed that the chestnut wood presented the highest content of extractives, while the Klason and total lignin contents were higher in the oak wood. A highly significant effect from the tablets was found on the extractives and Klason lignin contents, while the soluble lignin content was more affected by the staves. Oxygenation of the wine brandies during the aging process negatively affected the release of extractives and lignin from the wood to the brandy, and therefore will impact the overall quality of the brandy.